2020
DOI: 10.1016/j.scitotenv.2020.139864
|View full text |Cite
|
Sign up to set email alerts
|

Changes in U.S. air pollution during the COVID-19 pandemic

Abstract: The COVID-19 global pandemic has likely affected air quality due to extreme changes in human behavior. We assessed air quality during the COVID-19 pandemic for fine particulate matter (PM 2.5 ) and nitrogen dioxide (NO 2 ) in the continental United States from January 8th-April 21st in 2017–2020. We considered pollution during the COVID-19 period (March 13–April 21st) and the pre-COVID-19 period (January 8th-March 12th) with 2020 representing ‘current’ data and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

34
405
1
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 554 publications
(456 citation statements)
references
References 10 publications
(9 reference statements)
34
405
1
16
Order By: Relevance
“…Consequently, the economy of countries that depend on their exports has been severely affected ( ECLAC, 2020 ). Furthermore, the reduction in transport has caused decreases of 17% in the global CO 2 emissions ( Le Quéré et al, 2020 ), 30% in NO 2 emissions in COVID-19 epicentres such as Wuhan, Italy, and USA ( Muhammad et al, 2020 ; Wang et al, 2020 ; Gautam, 2020a ), as well as 62% in Spanish cities ( Baldasano, 2020 ), 25.5% in PM 2.5 particles in USA ( Berman and Ebisu, 2020 ), and a 20 years low in the concentration of aerosol particles in India ( Gautam, 2020b ) compared to pre-pandemic levels. Also, there has been an increase of 24% ozone in southern European cities ( Sicard et al, 2020 ) and 17% in India ( Sharma et al, 2020 ), Hence, keeping track of these and other changes in our environment during the COVID-19 pandemic is a useful practice to obtain feedback of the event itself and the measures applied in order to plan future strategies, especially since there are recent reports that show evidence of the virus RNA in wastewater, ( Ahmed et al, 2020 ) as well as a correlation between the number of COVID-19 deaths to the diurnal temperature range ( Ma et al, 2020 ) and other climate conditions ( Coccia, 2020 ; Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the economy of countries that depend on their exports has been severely affected ( ECLAC, 2020 ). Furthermore, the reduction in transport has caused decreases of 17% in the global CO 2 emissions ( Le Quéré et al, 2020 ), 30% in NO 2 emissions in COVID-19 epicentres such as Wuhan, Italy, and USA ( Muhammad et al, 2020 ; Wang et al, 2020 ; Gautam, 2020a ), as well as 62% in Spanish cities ( Baldasano, 2020 ), 25.5% in PM 2.5 particles in USA ( Berman and Ebisu, 2020 ), and a 20 years low in the concentration of aerosol particles in India ( Gautam, 2020b ) compared to pre-pandemic levels. Also, there has been an increase of 24% ozone in southern European cities ( Sicard et al, 2020 ) and 17% in India ( Sharma et al, 2020 ), Hence, keeping track of these and other changes in our environment during the COVID-19 pandemic is a useful practice to obtain feedback of the event itself and the measures applied in order to plan future strategies, especially since there are recent reports that show evidence of the virus RNA in wastewater, ( Ahmed et al, 2020 ) as well as a correlation between the number of COVID-19 deaths to the diurnal temperature range ( Ma et al, 2020 ) and other climate conditions ( Coccia, 2020 ; Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lockdown of the production sectors, restriction on human mobility, and controlled public transportation system have resulted in the lowering of emission of pollutants. Studies by various scholars have shown how the lockdown has improved the ambient air quality, like in India (Gautam 2020 ; Mahato et al 2020 ; Sikarwar and Rani 2020 ; Srivastava et al 2020 ), the USA (Berman and Ebisu 2020 ), Mexico (Méndez-Arriaga 2020 ), Kazakhstan (Kerimray et al 2020 ), Iran (Abdul Halim et al 2018 ), China (Fan et al 2020 ; Zambrano-monserrate et al 2020 ) especially in Wuhan (Cole et al 2020 ; Lu et al 2020 ; Sicard et al 2020 ; Song et al 2016 ; Wang and Su 2020 ), Barcelona in Spain (Tobías et al 2020 ), Sao-Paulo in Brazil (Nakada and Urban 2020 ), Milan in Italy (Collivignarelli et al 2020 ), and Salé City in Morocco (Otmani et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…By mid-June 2020, the pandemic encompassed more than 8 million infected people and nearly 450,000 deaths around the world. This pandemic has greatly affected human society, including health care, social relationships, and the structure of the economy as well as politics (Berman and Ebisu 2020 ).…”
Section: Introductionmentioning
confidence: 99%